'I was there from the start': The identity-maintenance strategies used by fans to combat the threat of losing. Issue 2 (April 2017) - Doyle, Jason P.; Lock, Daniel; Funk, Daniel C.; Filo, Kevin; McDonald, Heath
Highlights: We focus on identity-maintenance strategies employed in the face of group threat. Results evidence the use of social creativity and social mobility tactics. Enhancing the team's future prospects and the individual's group position provides protection from identity threats. Abstract: On-field performances are a key, yet uncontrollable, determinant of team identification. In this research, we explore how fans of a new team, with an overwhelming loss to win ratio, maintain a positive social identity. Qualitative data gathered from 20 semi-structured interviews were used to address this research objective. Our findings indicated fans use social creativity and social mobility strategies to help preserve a positive and distinctive group identity. In the absence of success, fans evaluated the group on dimensions that reflected positively on, and emphasised the distinctiveness of, group membership. Fans also sought to increase their status in the group to increase the positivity of this association. We use these findings to extend understanding of social identity theory and provide recommendations for sport organisations with unfavourable performance records. Recommendations are themed around highlighting the unique nature of the group and favourable status comparisons between members of the in-group.